FAKTOR PENYEBAB TIDAK BERFUNGSINYA PERATURAN NAGARI DIBIDANG AGAMA JORONG KOTO TANGAH NAGARI PEMATANG PANJANG KECAMATAN SIJUNJUNG KABUPATEN SIJUNJUNG - RAHMAN, MELATI - (Pendidikan Sosiologi, 2014)
Various behavioral phenomena that do not fit the norm among teenagers, one of the teenagers in the North West who do not follow the rules that have been prepared in the country dike length. In accordance with the Rules of Order No. 02 of 2008, article 6 section 4 villages Long Causeway has regulations in the field of religion, namely, all children aged 7-16 years (elementary through high school) will be required to the mosque. For children who roam at the mosque would be arrested by the Police Community Safety Forum (FKPM), then secured and processed / settled in the Office of the State, when the same child twice processed at the Office of the State concerned parents will be given sanctions collaboration 1 working day. This rule applies to the year 2008, therefore, the problem is the number of children who violate the rules of the country in the field of religion requires children aged 7-16 years of study to the mosque. This problem describes "the factors causing the failure of state regulation in the field of religious corner villages Long hands dike length". The theory used in this study is the structural functional developed by Robert K. Merton. As this study used a qualitative approach which is defined as the perception perceived by others, understand the mindset and perspective of others. Informants in this study is that people around the corner Koto hands, parents of children who violate the countrys North Long, head of the youth of the land dike Long, Long Causeway land trustee, chairman of the Police Community Safety Forum (FKPM), children aged 7 -16 years using purposive sampling of 14 people. While the collection of data through observation (non-participant), interviews, and documentation. Data were analyzed using Miles and Hubermans model consists of data reduction, data display, and conclusion. Based on the research that has been carried out revealed that the cause of the failure of state regulation in the field of religion. Malfunction Security Community Police Forum (FKPM), the less control and supervise children in violation of state regulations in the field of religion.